2021
DOI: 10.12688/f1000research.53689.2
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with knowledge, attitudes and preventive practices towards COVID-19 in health care professionals in Lima, Peru

Abstract: Background: Nowadays, we are facing a disease caused by SARS-CoV-2, known globally as COVID-19, which is considered a threat to global health due to its high contagiousness and rapid spread. Methods: Analytical cross-sectional study in 302 health professionals. An online questionnaire consisting of questions about knowledge, attitudes and practices (KAP) towards COVID-19 was applied. Socio-demographic, occupational and comorbidities factors were explored. Simple and multiple logistic regression models were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
(18 reference statements)
2
2
0
Order By: Relevance
“…Our multivariate analysis indicated that individuals with more accurate knowledge and more positive attitudes had more frequent best practices than their counterparts. These findings corroborate previous studies in South Korea, China, Malaysia, Nigeria, and Peru, which reported that sufficient knowledge is necessary for more positive attitudes and more frequent best practices during the pandemic [ 24 , 25 , 26 , 28 , 29 ]. However, the findings contradict a study in Ecuador, Iran, and Bangladesh, and a prior study in Indonesia, both of which found discrepancies in this area [ 4 , 23 , 30 , 31 , 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our multivariate analysis indicated that individuals with more accurate knowledge and more positive attitudes had more frequent best practices than their counterparts. These findings corroborate previous studies in South Korea, China, Malaysia, Nigeria, and Peru, which reported that sufficient knowledge is necessary for more positive attitudes and more frequent best practices during the pandemic [ 24 , 25 , 26 , 28 , 29 ]. However, the findings contradict a study in Ecuador, Iran, and Bangladesh, and a prior study in Indonesia, both of which found discrepancies in this area [ 4 , 23 , 30 , 31 , 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, this also underscores that there is a need to conduct social and behavioral change communication interventions that target all community members regardless of their age category to adhere to the preventive measures. Similarly, this finding was supported by a study conducted among educated persons and health professionals in Peru and Ethiopia ( 17 19 ). On the other hand, the present finding was contrary to the study performed in Egypt which revealed that young age was a good protective age ( 20 ).…”
Section: Discussionsupporting
confidence: 65%
“…As a result, their knowledge scores may be higher. Conversely, there have been reports that no association exists between gender and knowledge in KAP surveys conducted with healthcare professionals [ 28 , 38 , 39 ]. It has been speculated that this is because healthcare workers are involved in COVID-19 infection control regardless of gender.…”
Section: Discussionmentioning
confidence: 99%